An endemic coralsnake mimic: a new state record of Sonora michoacanensis (Dugès, 1885) (Squamata, Colubridae) in Central Mexico - Lizeth Solano-García; Gabriel Suárez-Varón; Aldo Gómez-Benitez; Gisela Granados-González; Oswaldo Hernández-Gallegos (Check List)
Sonora michoacanensis (Dugès, 1885), Michoacan Groundsnake (Squamata, Colubridae) is a non‑venomous snake endemic to Mexico, distributed across the Depresión del Balsas and along the Pacific Coast in the states of Morelos, Puebla, Guerrero, Michoacán, Colima, and Jalisco. We present the first record of this species from the State of Mexico. The new record fills a gap in the known distribution of S. michoacanensis in Central Mexico, and increases the number of known colubrid species to 23 and the total number of reptile species in the State of Mexico to 104.